Brood pouch evolution in pipefish and seahorse based on histological observation. (24th March 2022) - Harada, Akari; Shiota, Ryotaro; Okubo, Ryohei; Yorifuji, Makiko; Sogabe, Atsushi; Motomura, Hiroyuki; Hiroi, Junya; Yasumasu, Shigeki; Kawaguchi, Mari
Abstract: Introduction: Fishes of the Syngnathidae family are rare in having male pregnancy: males receive eggs from females and egg development occurs in the male brood pouch that diverged during evolution. The family is divided into two subfamilies: Nerophinae and Syngnathinae. Methods: We compared histologically five types of the brood pouch in Syngnathinae: an open pouch without skinfolds (alligator pipefish); an open pouch with skinfolds (messmate pipefish); a closed pouch with skinfolds (seaweed pipefish); and closed pouches with a sac-like pouch on the tail (pot-bellied seahorse) or within a body cavity (Japanese pygmy seahorse). Results: Histological observations revealed that all the examined species possess vascular egg compartments during the brooding period. The present immunohistochemical study revealed that the pregnant egg compartment epithelium grows thin in both open and closed pouches. The placenta of open and closed pouches is composed of dermis and reticulin fibers, respectively. The closed pouch placenta is a flexible and moist tissue, suitable for substance transport between the father and embryos through the epithelium and blood vessels and responsible for supplying nutrition and removing waste. Discussion: These results suggest that the basic egg incubation structures were established at an early stage of Syngnathinae evolution. On the other hand, it is likely that the innovation of tissue structure, where dermis was replaced with reticular fibers, occurred in closed brood pouches to regulate the pregnant pouch environment. The present study presents the morphological evolutionary pathway of the brood pouch in Syngnathinae, providing a basis for further molecular-level evolutionary studies. Highlights: Brood pouches of syngnathid fishes possess several common features. Brood pouches are egg compartments with blood vessels and thin luminal epithelium. Substitution of placental tissue occurred during evolution. Reticular fibers are the main placenta component in closed pouches. The first histological observation of the pygmy seahorse brood pouch is presented.